(untitled) (Journal of Mechanical Engineering, 2017)
The paper presents, the multigrid method for the solution of combined effect of surface roughness and viscosity variation on the squeeze film lubrication of a short journal bearing operating with micropolar fluid. The modified Reynolds equation which incorporates the variation of viscosity in micropolar fluid is analysed using Multigrid method. The governing modified Reynolds equation is solved numerically for the fluid film pressure and bearing characteristics viz. load carrying capacity and squeeze time. The analysis of the results predicts that, the viscosity variation factor decreases the load carrying capacity and squeeze film time, resulting into a longer bearing life. The results are compared with the corresponding analytical solutions.